Reaching the Limit of Inverted Solvatochromism in π-extended Bipyridinium-Phenolate Dyes - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M (American Chemical Society, 2025)
A series of pi-extended bipyridinium-N-phenolate dyes were synthesized to examine the combined effects of pi-extension and a second pyridinium unit on solvatochromism. The UV-vis spectral behavior of all dyes follows an inverted solvatochromic tendency, with absorptivity values depending on the viscosity of the media due to reduced planarity. TDDFT calculations reproduced the spectra and clarified the charge-transfer pathways, highlighting the critical role of planarity and conjugation in tuning solvatochromic responses.